2020
DOI: 10.1007/s12282-020-01111-1
|View full text |Cite
|
Sign up to set email alerts
|

SNORA71B promotes breast cancer cells across blood–brain barrier by inducing epithelial-mesenchymal transition

Abstract: Background Brain metastasis (BM) is a dreadful complication that significantly impacts the quality of life in breast cancer patients. A key process during brain metastasis is the migration of cancer cells across blood–brain barrier (BBB). However, the role of snoRNAs regulating BBB in BM is still unknown. Methods Here SNORic and GEO databases were used to identify differentially expressed snoRNAs between brain metastatic and non-metastatic breast cancer (BC) tissues. The effects of SNORA71B on the capacities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…And amongst the top rhythmic snoRNAs are included families with switches across the tissues we considered (3/20 (50% of the snoRNAs) top rhythmic transcripts are snoRNAs (SNORA14B, SNORD115–1 and SNORA71B) from families with switches), suggesting families with capacity for variation in the abundance of members could be used by the cell in processes including the regulation of diurnal rhythms. Interestingly, from these three snoRNAs, SNORD115 members were shown to be involved in the alternative splicing of the serotonin receptor 2C gene [ 56 ] while SNORA71B was shown to promote proliferation, migration and invasion of breast cancer cells [ 57 ]. From that perspective, it is not impossible that switches in expression of family members could be used to modulate the efficiency of non-canonical functions of snoRNAs, while maintaining canonical functions.…”
Section: Discussionmentioning
confidence: 99%
“…And amongst the top rhythmic snoRNAs are included families with switches across the tissues we considered (3/20 (50% of the snoRNAs) top rhythmic transcripts are snoRNAs (SNORA14B, SNORD115–1 and SNORA71B) from families with switches), suggesting families with capacity for variation in the abundance of members could be used by the cell in processes including the regulation of diurnal rhythms. Interestingly, from these three snoRNAs, SNORD115 members were shown to be involved in the alternative splicing of the serotonin receptor 2C gene [ 56 ] while SNORA71B was shown to promote proliferation, migration and invasion of breast cancer cells [ 57 ]. From that perspective, it is not impossible that switches in expression of family members could be used to modulate the efficiency of non-canonical functions of snoRNAs, while maintaining canonical functions.…”
Section: Discussionmentioning
confidence: 99%
“…They can separate from the primary tumour and enter the nearby blood and lymphatic vessels, and then reach the parenchymal tissue to form small cancer cell nodules 47. Accumulating studies show that some sncRNAs can functionally regulate the metastatic ability of cancer cells 64–68. In gastric cancer, tRF-3017A from tRNA-Val-TAC negatively regulates the expression of tumour suppressor gene NELL2 by forming RNA-induced silencing complex with AGO2, so as to enhance the migration and invasion of gastric cancer cells 69.…”
Section: Biological Function Of Sncrnas In Cancermentioning
confidence: 99%
“…Increasing studies have shown the sncRNAs have great potential as a biomarker platform for tumour prognosis 62 65 67 92–95. Gao et al , through univariate COX regression analysis, showed that six snoRNAs (snoRA47, snoRA68, snoRA78, snoRA21, snoRD28 and snoRD66) are highly expressed and are associated with a lower overall survival rate in patients with non-small cell lung cancer 94.…”
Section: Clinical Significance Of Sncrnas In Cancermentioning
confidence: 99%
“…Cell adhesion molecule 2 (CADM2) induces BM by activating the EMT pathway in NSCLC [11]. SNORA71B, a type of SnoRNA, promotes the migration of breast cancer cells across the blood-brain barrier by activating the EMT pathway [12]. According to a previous study, the inhibition of EMT by cucurbitacin B, an HER2 target therapeutic substance, results in the inhibition of BM in breast cancer cells [13].…”
Section: Introductionmentioning
confidence: 99%